The Response of State Government Receipts to Economic Fluctuations and the Allocation of Counter-Cyclical Revenue Sharing Grants - Vogel, Robert C.; Trost, Robert P. (The Review of Economics and Statistics, 1979)
Robert C. Vogel, Robert P. Trost, The Response of State Government Receipts to Economic Fluctuations and the Allocation of Counter-Cyclical Revenue Sharing Grants, The Review of Economics and Statistics, Vol. 61, No. 3 (Aug., 1979), pp. 389-400